Exploring Gender In The Dynamics Of The Efl Classroom At The Elementary School - Peña Figari, Elena María (2015)
In the last decades, several investigations have been carried out with relation to the way gender differences may impact the learning process. The present study seeks to clarify, not only such effect, but also what intervention tools and strategies teachers apply to handle gender diversity in the EFL classroom. With this purpose, the researcher worked with six specific groups of students, whose ages ranged between six and eleven years old, and their respective Language teachers together with the English Coordinator, the School Psychologist and the Discipline Inspector at an Ecuadorian bilingual school in the city of Guayaquil. Data was collected by means of a classroom observation instrument, students´ and teachers´ questionnaires, interviews and the analysis of school documents. Findings rendered and confirmed valuable information with relation to gender differences between boys and girls in aspects such as: attention span, class participation, need for supervision, students´ perceptions of their Language teacher, types of activities male and female pupils like or dislike, interaction with the opposite gender and teacher, to name a few. Likewise, this research has evinced the urgent need to provide special training to EFL educators with relation to the topic in question since the participating schoolteachers manifested not having been capacitated in this area.